Not One but Many: Monetary Punishment and the Fergusons of America1, 2. (31st July 2017) - Henricks, Kasey; Harvey, Daina Cheyenne
Abstract : How typical is Ferguson? That is, to what extent is monetary punishment driven by fiscal crisis and deficit spending? Do communities that increasingly rely less on property taxes generate higher rates of fines and fees? And how might increased spending on policing over time impact whether local governments turn to these sanctions for revenue? We compile city‐ and county‐level information from four national data sets to answer these questions through a series of least squares regression models. Our findings add to what sociologists, criminologists, and policymakers know about monetary punishment in at least three ways. First, we offer an analysis that focuses on monetary sanctions for not only criminal but civil courts. Second, our focus broadens the scope of local case studies that emphasize questions of process. And third, our study furthers the project of the New Fiscal Sociology. Throughout, we stress how public finance formalizes inequality in ways that define the symbolic relations between groups, their relation to the state, and the unspoken social contract. Our discussion concludes with some policy recommendations.